A Deoxygenative [4+1] Annulation Involving N‐Acyldiazenes for an Efficient Synthesis of 2, 2, 5‐Trisubstituted 1, 3, 4‐Oxadiazole Derivatives. Issue 22 (14th November 2017) - Zhou, Rong; Han, Ling; Zhang, Honghui; Liu, Rongfang; Li, Ruifeng
Abstract: An unprecedented and highly efficient tris(dimethylamino)phosphine [P(NMe2 )3 ]‐mediated deoxygenative [4 + 1] annulation of N ‐acyldiazenes with α‐dicarbonyl compounds such as isatins, α‐keto esters, and α‐diketones is reported. The annulation reactions proceed smoothly under mild conditions to deliver a broad range of 2, 2, 5‐trisubstituted 1, 3, 4‐oxadiazole derivatives in moderate to excellent yields from readily available starting materials. It represents the first realization of the [4+1] annulation mode involving N ‐acyldiazenes to construct five‐membered heterocycles. Abstract :